If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3b+3=2b+9
We simplify the equation to the form, which is simple to understand
3b+3=2b+9
We move all terms containing b to the left and all other terms to the right.
+3b-2b=+9-3
We simplify left and right side of the equation.
+1b=+6
We divide both sides of the equation by 1 to get b.
b=6
| r=1-3sinX | | 5q+6=2q-2+g | | 2(9x-7)+2(2x-6)= | | 2x^2+3x^2=84 | | 7(D-5)=12+5 | | -4(5x-5)+11x=3(-7x-9)-49 | | 12*sinx=6 | | 14x-8x=27 | | 6x-x-15= | | 5k-3(k-2)=-24 | | 5x^3-5x^2+12x=0 | | -4n-12=2+5n+4 | | 5m+5=10 | | 12cosx=6 | | 0=5r+6r | | Cx+8x-3y+7=0 | | .50r+5=1r | | 5y-1y=3 | | 2/5c+4-1.5c=-9 | | 7(n+5)-6=4(1+8n) | | 5-6n=5-6n | | 7b-5-5b=15-2b | | 4-5x=22 | | 0.45=logx | | 7+25x=38+18x | | -6-3y=2 | | 125m+75m+48000=50000-200m | | -n=-8+2n | | 7d+2=9d-5 | | 4-5=22 | | 9+6+4x+9=x | | 30+2x=40+1x |